1997
DOI: 10.1139/y97-060
|View full text |Cite
|
Sign up to set email alerts
|

Active 22Na+ transport by the intact lung during early postnatal life

Abstract: The lung relies upon epithelial active transport of Na+ to aid in the clearance of fluid from its air spaces. Because it is unknown whether the rate of active Na+ transport by the distal lung epithelium varies during early postnatal age, we performed studies in young guinea pigs (7 and 30 days after birth). We used a single pass isolated perfused lung model in which a Krebs Ringer bicarbonate solution containing 22Na+, [14C]sucrose, and FITC-dextran was placed into the air spaces of the lungs, and apparent per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Our present experiments are consistent with previous studies that show the presence of amiloride‐insensitive Na + transport pathways within the distal regions of the lung. Studies in single pass perfused lungs revealed amiloride‐insensitive 22 Na + and airspace fluid clearance (O'Brodovich et al 1997) and there is amiloride‐insensitive 22 Na + transport in acutely isolated bovine airway (Langridge‐Smith, 1986) and rabbit nasal epithelium (Ropke et al 1996). DLE grown in primary culture have variable amounts of Na + ‐dependent, amiloride‐insensitive I sc (O'Brodovich et al 1990) and human nasal epithelia have amiloride‐insensitive Na + conductive channels (Chinet et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Our present experiments are consistent with previous studies that show the presence of amiloride‐insensitive Na + transport pathways within the distal regions of the lung. Studies in single pass perfused lungs revealed amiloride‐insensitive 22 Na + and airspace fluid clearance (O'Brodovich et al 1997) and there is amiloride‐insensitive 22 Na + transport in acutely isolated bovine airway (Langridge‐Smith, 1986) and rabbit nasal epithelium (Ropke et al 1996). DLE grown in primary culture have variable amounts of Na + ‐dependent, amiloride‐insensitive I sc (O'Brodovich et al 1990) and human nasal epithelia have amiloride‐insensitive Na + conductive channels (Chinet et al 1993).…”
Section: Discussionmentioning
confidence: 99%